Simulations for Design and Manufacturing Select Papers from AIMTDR 2016 - Dixit, Uday S.; Kant, Ravi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on numerical simulations of manufacturing processes, discussing the use of numerical simulation techniques for design and analysis of the components and the manufacturing systems. Experimental studies on manufacturing processes are costly, time consuming and limited to the facilities available. Numerical simulations can help study the process at a faster rate and for a wide range of process conditions. They also provide good prediction accuracy and deeper insights into the process. The simulation models do not require any pre-simulation, experimental or analytical results, making them highly suitable and widely used for the reliable prediction of process outcomes. The book is based on selected proceedings of AIMTDR 2016. The chapters discuss topics relating to various simulation techniques, such as computational fluid dynamics, heat flow, thermo-mechanical analysis, molecular dynamics, multibody dynamic analysis, and operational modal analysis. These simulation techniques are used to: 1) design the components, 2) to investigate the effect of critical process parameters on the process outcome, 3) to explore the physics of the process, 4) to analyse the feasibility of the process or design, and 5) to optimize the process. A wide range of advanced manufacturing processes are covered, including friction stir welding, electro-discharge machining, electro-chemical machining, magnetic pulse welding, milling with MQL (minimum quantity lubrication), electromagnetic cladding, abrasive flow machining, incremental sheet forming, ultrasonic assisted turning, TIG welding, and laser sintering. This book will be useful to researchers and professional engineers alike. .
Design and Analysis of an Innovative Nozzle -- Distribution of Electromagnetic Field and Pressure of Single Turn Circular Coil for Magnetic Pulse Welding using FEM -- Computational Fluid Dynamics Analysis of MQL Spray Parameters and its Influence on MQL Milling of SS304 -- Pulse Electromagnetic Cladding of Al-Tube on DP Steel Rod -- Design, Development and Computational Analysis of Low Pressure Abrasive Flow Finishing Machine -- Dynamic Analysis of Robotic Manipulator for Incremental Sheet Metal Forming -- Finite Element and Experimental Study of Self-Reacting Friction Stir Welding of Aluminium Alloy AA6061-T6 -- Prediction of Critical Thinning during Self-Pierced Riveting of Sheets -- Numerical Prediction of Fracture in Parts formed with Incremental Sheet Forming Process -- Numerical Modeling of Micro-EDM Process using Finite Volume Method -- Experimental Studies and Numerical Simulations of a Displacement Amplifying Compliant Mechanism -- Study on the Delamination of GFRP Composites in Drilling: A Finite Element Model -- A Coupled Thermo-mechanical Model to Predict Forces, Temperature and Material Flow in Friction Stir Welding -- Improving Dynamic Stability of Machine Tool Structure with Operational Modal Analysis -- A Novel Approach for Prediction and Calculation of Sheet Thinning in Incremental Sheet Forming -- Studies on Springback Effect of TIG Welded Ti-6Al-4V Sheets -- Finite Element Analysis of V-shape Incremental ECAP -- Finite Element Method Analysis of Electrochemical Discharge Machine using Explicit Dynamics ANSYS -- Molecular Dynamics Simulation Study of Neck-growth in Micro-selective Laser Sintering of Copper Nanoparticles.
Keywords: Manufactures; Computer simulation; Security systems; Machines, Tools, Processes; Computer Modelling; Security Science and Technology